Pengaruh Variasi Waktu Kontak Tanaman Bayam Duri terhadap Adsorpsi Logam Berat Kadmium (Cd) - Mohamad, Erni (Jurnal Entropi, 2013)
Cadmium waste industrial processes are the result of carcinogenic materials. Target organ toxicity is the kidney and liver Cd. Cadmium waste treatment can be performed by adsorption method using a plant thorn spinach (Amaranthus spinosus L). This plant is used as an adsorbent because it contains a protein which has the amine group (-NH2), carboxyl (-COOH), as well sulfhydril group (-SH). Besides, the plant tissue contained a cell wall composed of cellulose, lignin containing hydroxyl group (-OH). These polar groups capable of binding heavy metals. The purpose of this study was to determine the absorption capacity of spinach plants to metal spikes cadmium (Cd) in tissues of roots, stems and leaves with a variation of contact time. Research carried out by the time variation of 2.4 and 6 on Sunday. Cd concentrations of metals found in plant tissues in the analysis using the method of atomic absorption Spectrophotometry (AAS) at a wavelength of 228.8 nm. The data obtained were then analyzed RAL. The highest order of Cd (II) adsorbed to the variation of time is a week to 2> 4> 6